Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,434 questions

17,804 answers

1,438 comments

48,261 users

F(x)=2x+5,g(x)=x^2-3,h(x)=7-x

+2 votes
compute (f-h)(4)(f-h)(4)=f(4)-h(4) evalution each separately and subtract
asked Feb 25, 2013 in ALGEBRA 2 by linda Scholar

1 Answer

+2 votes

f(x) = 2x + 5, g(x) = x2 - 3, h(x) = 7 - x

Take f(x) = 2x + 5

Substitute x = 4 in the f(x).

f(4) = 2(4) + 5 = 8 + 5 = 13.

Take h(x) = 7 - x

Substitute x = 4 in the h(x).3

h(4) = 7 - 4 = 3.

Let f - h = f(x) - h(x) = (2x + 5) - (7 - x) = 2x + 5 - 7 + x = 3x - 2.

(f - h)(4) = 3(4) - 2 = 12 - 2 = 10.

(f - h)(4)(f - h)(4) = (10)(10) = 100.

f(4) - h(4) = 13 - 3 = 10.

Therefore (f - h)(4) = f(4) - h(4)

But (f - h)(4)(f - h)(4) not equal to f(4) - h(4).

answered Feb 25, 2013 by britally Apprentice

Related questions

asked Oct 11, 2018 in ALGEBRA 2 by anonymous
...